Thực trạng quản lí hoạt động giáo dục giới tính cho học sinh ở các trường tiểu học công lập trên địa bàn quận Bình Tân, Thành phố Hồ Chí Minh - Lê, Chi Lan; Phạm, Thị Thu Hằng (Tạp chí Giáo dục, 2024)
Sex education for students is currently a matter of great interest from society; this is an important educational content in primary schools in order to equip students with basic knowledge about gender and reproductive health. Management of sex education activities for students in public primary schools plays an important role in improving the quality of sex education in primary schools, so the article explores the current state of sex education management in primary schools. To manage sex education activities for students in public primary schools, the author surveyed 10 public primary schools in Ho Chi Minh City with 90 teachers, 30 administrators at primary schools. Binh Tan District, Ho Chi Minh City. The results show that the actual management of sex education activities in public primary schools in Binh Tan District is still limited. Through the study, the article has proposed recommendations to improve the quality of management of sex education activities for students in public primary schools.